Emerging role for SRC family kinases in junction dynamics during spermatogenesis. Issue 3 (March 2019) - Xiao, Xiang; Yang, Yue; Mao, Baiping; Cheng, C Yan; Ni, Ya
Abstract : SRC family kinases (SFKs) are known regulators of multiple cellular events, including cell movement, differentiation, proliferation, survival and apoptosis. SFKs are expressed virtually by all mammalian cells. They are non-receptor protein kinases that phosphorylate a variety of cellular proteins on tyrosine, leading to the activation of protein targets in response to environmental stimuli. Among SFKs, SRC, YES and FYN are the ubiquitously expressed and best studied members. In fact, SRC, the prototypical SFK, was the first tyrosine kinase identified in mammalian cells. Studies have shown that SFKs are regulators of cell junctions, and function in endocytosis and membrane trafficking to regulate junction restructuring events. Herein, we briefly summarize the recent findings in the field regarding the role of SFKs in the testis in regulating spermatogenesis, particularly in Sertoli–Sertoli and Sertoli–germ cell adhesion. While it is almost 50 years since the identification of the oncogene v- Src encoded by Rous sarcoma transforming virus, the understanding of SFK involvement during spermatogenesis in the testis remains far behind that in other epithelia and tissues. The goal of this review is to bridge this gap.